Effect of Cow Manure Dosage and Biofertilizer Concentration on the Growth and Yield of Peanut Plants (Arachis hypogaea L.) - Ginanjar, Husni; Amalia, Lia; Mulyana, Hudaya (Institute of Computer Science (IOCS), 2022)
The experimental research was carried in Dawuan Kidul Village, Dawuan District, Subang Regency with an altitude of 92 m above sea level, with a type C climate (slightly wet) from August 2022 to October 2022. This study aims to study the interaction effect of cow manure application and the concentration of biological fertilizers. Environmental design using a completely randomized design (RAK) factorial pattern, with treatment of cow manure and biological fertilizer. Cow manure (K) consists of 4 levels, namely k0 = 0 tons ha?¹ (control), k1 = 10 tons ha? ¹ k2 = 20 tons ha?¹, k3 = 30 tons ha?¹ and bio-fertilizer bio-extreme (Y) consists of 4 levels, namely y0 = 0 ml L? ¹ water (control ) or equivalent to 0 liters of bio-extreme biofertilizer ha?¹ y1 = 2.5 ml L? ¹ water or equivalent to 0.5 liters ha?¹ bio-extreme biofertilizer ha?¹ y2 = 5 ml L? ¹ water or the equivalent of 1 liter of bio-extreme biofertilizer ha?¹ y3 = 7.5 ml L?¹ of water or the equivalent of 1.5 liters of bio-extreme biofertilizer ha?¹. The results showed that the effect of cow manure and biological fertilizers had an interaction effect on plant height at 14 days after planting and the number of branches at 28 days after planting, while observing the number of leaves, number of pods planted, total pod weight and number of pods per plot showed no interaction